Someday - Kingsbury, Karen (Kingsbury, Karen. Sunrise series, 2008)
Pressures of the celebrity lifestyle weigh heavily on Dayne and Katy Matthews as they take on separate movie projects. Tabloid rumors talk of trouble and unfaithfulness between the two, but finally something drastic catches Daynes attention and makes him realize the destruction theyre playing with. But will it be too late? The Flanigan family recognizes the deep loss of the Christian Kids Theater program, and they lead a final effort to keep the theater from being torn down. Meanwhile, John Baxter takes the next step in his growing relationship with Elaine, giving him a season to contemplate selling the Baxter house and, along with it, losing a lifetime of memories made there. As the rest of the family considers the future and what may lie ahead, they must pull together like never before. Only their undying love for each other can help the Baxters get past the trials of today for a life they know is possible . . . someday.